Heroin Inhibits HIV-Restriction miRNAs and Enhances HIV Infection of Macrophages - Wang, Xu; Ma, Tong-Cui; Li, Jie-Liang; Zhou, Yu; Geller, Ellen B.; Adler, Martin W.; Peng, Jinsong; Zhou, Dun-Jin; Zhou, Wang; Ho, Wen-Zhe (Frontiers in Microbiology, 2015)
Although opioids have been extensively studied for their impact on the immune system, limited information is available about the specific actions of opioids on intracellular antiviral innate immunity against HIV infection. Thus, we investigated whether heroin, one of the most abused drugs, inhibits the expression of intracellular HIV restriction microRNA (miRNA) and facilitates HIV replication in macrophages. Heroin treatment of macrophages enhanced HIV replication, which was associated with the downregulation of several HIV restriction miRNAs. These heroin-mediated actions on the miRNAs and HIV could be antagonized by naltrexone, an opioid receptor antagonist. Furthermore, the in vitro negative impact of heroin on HIV-associated miRNAs was confirmed by the in vivo observation that heroin addicts had significantly lower levels of macrophage-derived HIV restriction miRNAs than those in the control subjects. These in vitro and in vivo findings indicate that heroin use compromises intracellular anti-HIV innate immunity, providing a favorable microenvironment for HIV survival in the target cells.